The Relationship Between Self-Efficacy and Student’s Academic Procrastination in Completing Their Final Project - Siti Nurrochmah Budiyati; Ervan Johan Wicaksana; Upik Yelianti (Research, Training and Philanthropy Institution Natural Aceh, 2026)
This study examines the relationship between self-efficacy and academic procrastination in completing final assignments among university students. A quantitative approach with simple linear regression analysis was employed. The participants consisted of 47 Biology Education students at the University of Jambi who were completing their final projects. Data were collected using validated self-efficacy and academic procrastination scales. The findings revealed that both self-efficacy (79%) and academic procrastination (72%) were at moderate levels. Regression analysis indicated that self-efficacy significantly influenced academic procrastination (p < 0.005), contributing 47.6% to the variance. Interestingly, the positive regression coefficient suggests a potential overconfidence effect, where higher self-efficacy may lead to delayed task completion due to underestimation of task demands. This finding highlights that self-efficacy alone is insufficient to ensure productive academic behavior without adequate self-regulation. The study implies that universities should integrate psychological support and time management training to optimize students’ academic performance and reduce procrastination during the final assignment process.